Perjuangan Kesetaraan Gender Tokoh Wanita Dan Nilai Pendidikan Dalam Novel Gadis Kretek Karya Ratih Kumala - Maftuhah; Siti Aminah; Alfi Nur Haqiqi; Rohmatul Ummah (jurnal Mahasiswa Pencerah, 2022)
This study aims to describe and explain: (1) the struggle for gender equality of female characters in Ratih Kumala's novel Kretek Girl, and (2) educational values in Ratih Kumala's novel Kretek Girl.This type of research is qualitative research. This study used descriptive qualitative method. Qualitative descriptive method is a research procedure that produces description data in the form of words. The research data is a novel by Kretek Girl by Ratih Kumala.This study uses a feminism approach to describe the profile of female characters, the struggle for gender equality, and the sociological approach of literature to find out about the social conditions of the community in Ratih Kumala's novel Kretek Girl. The data collection technique used in this study was to read the entire contents of the novel and document analysis.The results of this study are as follows: (1) The struggle for gender equality of female leaders in Ratih Kumala's novel Kretek Gadis is against forms of gender injustice in the form of (a) stereotypes, (b) marginalization of women, (c) subordination of work, and (d) internal violence household. (2) Ratih Kumala's novel Kretek Girls educational values include: (a) the value of religious education that emphasizes between humans and God, (b) the value of social education refers to the relationship of individuals to other individuals in a society (c) the value of education morals that relate to the good or bad of human behavior, and (d) the value of cultural / customary education that is related to tradition, people's habits.